Multifactor Keynesian models of the long-term interest rate - Tanweer Akram (Levy Economics Institute of Bard College, 2021)
Using panel data models, we analyze the flypaper effects-whether intergovernmental fiscal transfers or states' own income determine expenditure commitments - on ecological fiscal spending in India. The econometric results show that the unconditional fiscal transfers, rather than the states' own income, determine ecological expenditure in the forestry sector at subnational levels in India. The results hold when the models are controlled for ecological outcomes and demographic variables.
Keywords: E12; E43; E50; E58; E60; G10; G12; G41; 330; Long-Term Interest Rate; Government Bond Yields; Monetary Policy; Short-Term Interest Rate; Inflation; Inflation Target; John Maynard Keynes